Hamzah Fansuri’s Mystical Poetry: An Analysis of Early Islamic Intellectualism and Sufistic Expression in the Malay Archipelago - Wijaya Wijaya (Journal of Noesantara Islamic Studies, 2025)
Hamzah Fansuri, one of the earliest Malay Sufi poets, represents a significant intellectual and spiritual synthesis in the history of Islamic thought in the Malay Archipelago. His poetry, infused with metaphysical symbolism and Sufistic language, serves as a reflection of the deep assimilation of Islamic mysticism into local cultural and linguistic contexts. This study aims to analyze the mystical dimensions and intellectual foundations of Hamzah Fansuri’s works to understand their role in shaping early Islamic intellectualism in Southeast Asia. A qualitative textual analysis was employed, focusing on hermeneutic interpretation and semiotic examination of selected verses from his syair and rubaiyat. The findings reveal that Hamzah Fansuri’s writings embody the principles of wahdat al-wujud (unity of existence), while simultaneously integrating Malay linguistic aesthetics and metaphors of maritime culture. His intellectualism is marked by a synthesis between Islamic metaphysics, local cosmology, and poetic expression. The research concludes that Hamzah Fansuri’s mystical poetry not only symbolizes the indigenization of Islamic thought but also represents an early articulation of philosophical discourse in the Malay literary tradition. The study reaffirms his position as a foundational figure in bridging Islamic intellectualism and cultural creativity in the region.